2016
DOI: 10.1080/0735648x.2016.1226931
|View full text |Cite
|
Sign up to set email alerts
|

The crime prevention effect of CCTV in public places: a propensity score analysis

Abstract: This study measures the effect of CCTV in Newark, NJ across three separate crime categories: auto theft, theft from auto, and violent crime. CCTV viewsheds, denoting camera line-of-sight, were units of analysis. Viewsheds for treatment units were created by digitizing live CCTV footage within a geographic information system (GIS). Control viewsheds were created with GIS tools and aerial imagery from Google maps. Treatment cases were matched with control cases via propensity score matching (PSM) to ensure stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 56 publications
0
47
0
1
Order By: Relevance
“…This was accomplished via the microsynthetic control method , which has been applied in similar fashion recently in evaluations of place‐based interventions (Connealy, Piza, & Hatten, 2019; Robbins, Saunders, & Kilmer, 2017; Rydberg, McGarrell, Norris, & Circo, 2018; Saunders, Lundberg, Braga, Ridgeway, & Miles, 2015). This was used, as opposed to propensity score matching (e.g., Braga, Hureau, & Papachristos, 2012; Haberman, Clutter, & Henderson, 2018; Piza, 2018a; Zakrzewski, Wheeler, & Thompson, 2019), mainly because street units subjected to the treatment are clustered into one area, so it does not make sense to evaluate crime reductions from street unit to street unit. Rather, it is more appropriate to calculate an overall crime reduction due to the substation, as well as to draw a statistically equivalent control area that mimics pre‐intervention crime trends, while being similar in its demographics and aspects of the built environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was accomplished via the microsynthetic control method , which has been applied in similar fashion recently in evaluations of place‐based interventions (Connealy, Piza, & Hatten, 2019; Robbins, Saunders, & Kilmer, 2017; Rydberg, McGarrell, Norris, & Circo, 2018; Saunders, Lundberg, Braga, Ridgeway, & Miles, 2015). This was used, as opposed to propensity score matching (e.g., Braga, Hureau, & Papachristos, 2012; Haberman, Clutter, & Henderson, 2018; Piza, 2018a; Zakrzewski, Wheeler, & Thompson, 2019), mainly because street units subjected to the treatment are clustered into one area, so it does not make sense to evaluate crime reductions from street unit to street unit. Rather, it is more appropriate to calculate an overall crime reduction due to the substation, as well as to draw a statistically equivalent control area that mimics pre‐intervention crime trends, while being similar in its demographics and aspects of the built environment.…”
Section: Methodsmentioning
confidence: 99%
“…As is the case with any police agency, the NPD has made numerous efforts to control crime at high‐crime places. As such, any targeted police intervention represents the latest attempt to control crime rather than a newfound interest in doing such, which matching algorithms should account for (Piza, 2018a). Pre‐enforcement actions were included to reflect the level of law enforcement activity within each street unit during the 3‐year pre‐intervention period 7…”
Section: Methodsmentioning
confidence: 99%
“…Scott et al (2016) measured the purchase and injection of heroin in public settings through a survey of intravenous drug users. 2 Piza (2018a) was originally published as an early view article in 2016, thus, falling within our search period.…”
Section: Conclusion and Directions For Policy And Researchmentioning
confidence: 99%
“…The experimental strategy generated statistically significant, and sizable, reductions of violent crime and social disorder. This is noteworthy in light of CCTV's limited effect on most street-level crime types, as observed in Newark (Caplan et al, 2011;Piza, 2014;Piza et al, 2014a) as well as in the general CCTV literature (Welsh & Farrington, 2009). The findings directly support the hypothesis that the integration of CCTV with proactive police activity generated by human operators produces a crime control benefit greater than what has previously been achieved via "stand-alone" camera deployment (Piza et al, 2014d).…”
Section: The Importance Of Human Factors In Technology Evaluations: Amentioning
confidence: 93%
“…Piza (2014) found that the full CCTV system generated modest auto theft reductions in only one of four police precincts while less than half (54 of 146) of the individual camera sites showed any evidence of an auto theft reduction (Piza et al, 2014a). None of the other 5 crime types included in the study experienced any significant reductions (Piza, 2014).…”
Section: The Importance Of Human Factors In Technology Evaluations: Amentioning
confidence: 99%